Two new species of alcyonacean-associated shrimp genus Alcyonohippolyte Marin, Okuno & Chan, 2010 (Crustacea: Decapoda: Hippolytidae) from the Great Barrier Reef of Australia - Marin, Ivan (Zootaxa, 2011)
Two new species of symbiotic hippolytid shrimps of the genus Alcyonohippolyte Marin, Okuno & Chan, 2010 are described from Lizard Island, the Great Barrier Reef of Australia. Alcyonohippolyte tenuicarpus sp. nov. is associated with xeniid soft coral of the genus Heteroxenia Kolliker, 1874 and differs from the congeners by a long rostrum greatly exceeding antennular peduncle and slender carpal segments of pereiopod II. Alcyonohippolyte tubiporae sp. nov. is associated with organ pipe coral of the genus Tubipora Linnaeus, 1758, possibly T. musica Linnaeus, 1758 (Alcyonacea: Tubiporidae), and differs from the congeners by equal distal and proximal carpal segments of pereiopod II. Both species can be clearly separated from the congeners ecologically and by coloration.